Situational perceived competence and choice when using digital technology in an inquiry-based learning setting in arts and crafts. (25th March 2019) - Heindl, Manuela
Although there is evidence of an improvement in pupil's learning achievements in inquiry-based learning sessions compared to traditional lessons, the influence of technology, especially in primary schools, has not yet been analysed yet. The question is, whether inquiry-based learning with digital technology leads to better outcomes, which will be indirectly measured through the final product and the pupil's perceived and choice. The latter is part of the intrinsic motivation, which can also improve pupil's scores according to Deci and Ryan. The treatment group used digital technology to solve a scientific architectural problem in the creative subject 'arts and crafts' and the control group used worksheets instead. The pupils were given the standardised intrinsic motivation inventory questionnaire by Deci and Ryan. The Whitney-Mann U -test concluded that the treatment group felt more competent ( U = 4, 149, p = 0.006) than the control group and reported a desired teaching effect ( d = 0.419) but there was no significance for pupil's perceived choice ( U = 5, 019, p = 0.514). There was a weak but positive correlation between 207 pupil's successful product and their situational perceived competence ( rs = 0.299, p = 0.001), but no significance for perceived choice ( rs = 0.133, p = 0.057).